(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The analysis of water discharge frequency for Diyala river D/S Derbendi-Khan Dam have been computed using some statistical models such are " Gumbel, Pearson III, log Pearson III and log-normalIII. The models were‏ applied to annual water discharge for Diyala river. The water discharge magnitudes computed for many return periods‏ . Firstly, The models were Compared using different statistical measures " bias, standard error and root mean square error. The Chi-Square test was used to evaluate the goodness of fits for these models. According to this test and using the aforementioned measures, the Log-Normal III distribution could be taken as the best for the water discharge series. This type of model is useful for designing the dam or spillway by computing the magnitude of water discharge flood versus different return periods.